Reform of the Trial Courts in Quebec - Huguette St-Louis (Canada's Trial Courts, 2007)
I am one of those who believe that the courts are not static institutions. On the contrary, they must adapt to the expectations of the system’s users. In an article published in 2000 in theCanadian Bar Review, Judge Gerald Seniuk and Professor Noel Lyon showed that the development of the Provincial Courts raises many problems, not the least of them being the tendency of the system to evolve in a way that no longer fits the constitutional framework.¹ In this context, and in light of concrete examples and the reflections of experts, we must be particularly attentive to this